Monitoring and Control of a Remote Hybrid Powered Reverse Osmosis Unit for McCallum, NL - Kafrashi, Fatemeh; Golchin, Hani; Iqbal, M. Tariq (Journal of Electronics and Electrical Engineering, 2025)
This study presents the design and implementation of a low-cost, fully offline Supervisory Control and Data Acquisition (SCADA) system for monitoring and controlling a Reverse Osmosis (RO) water treatment unit powered by a Hybrid Energy System (HES) in the remote community of McCallum, Newfoundland and Labrador. The HES comprising PV panels, a wind turbine, batteries, and a DC diesel generator was designed and validated in prior work. To address the lack of Internet and cellular connectivity, the proposed system combines Long-Range (LoRa) communication with a local Message Queuing Telemetry Transport (MQTT) broker to facilitate real-time monitoring and bidirectional control. Two ESP32 LoRa modules form the hardware backbone, enabling wireless data transmission and control across a 400-meter range. Sensor data is visualized through FUXA, an open-source, web-based SCADA platform hosted locally. The system also provides audible alerts for fault conditions. Seven operational scenarios were tested to evaluate system performance, confirming reliable data acquisition, robust wireless communication, and effective remote actuation. Lab tests showed average end-to-end latency of 200–300 ms, zero packet loss in line-of-sight conditions, and a field-unit power demand of 21–22 Wh/day. The modular architecture supports scaling to multiple RO units or larger communities without requiring Internet connectivity. The proposed architecture offers a scalable, energy-efficient, and Internet-independent SCADA solution for critical infrastructure in disconnected and resource-limited environments.